REPRESENTATION OF HEGEMONIC IDEOLOGY IN AYU UTAMI'S NOVEL SAMAN: A CRITICAL DISCOURSE ANALYSIS STUDY - Sa’adiyah, Evha Nazalatus (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT This study aims to reveal the representation of hegemonic ideology in the novel Saman by Ayu Utami through Critical Discourse Analysis approach. The novel Saman was chosen as the object of study because of the Indonesian socio-political context during the Reformation period, which is full of ideological conflicts, especially regarding patriarchal domination, conservative religion, and the struggle for individual freedom. Through a qualitative method, data were collected using in-depth reading and thematic coding techniques on narrative excerpts, dialogues, and descriptions that reflect ideological power. The results show that hegemonic ideology is strongly represented through the main characters and the storyline, which illustrates the tension between the restrictive social structure and the individual's efforts to achieve freedom of thought and action. Discursive strategies, such as the use of metaphors, critical dialogue, and multivocal narratives, reinforce critiques of ideological domination. The novel also features a socio-political dimension that is closely related to the conditions of Indonesia, especially how the hegemonic ideologies of religion and patriarchy function as a means of control and power reproduction. In addition, elements of resistance and subversion emerge through the characters’ critical attitudes and actions that reject absolute obedience and seek to transform the social order. The findings confirm that ideological power is not absolute, and literature can be an important medium for social reflection and resistance. This research provides theoretical contributions to literary studies and discourse analysis, as well as practical implications for understanding the relationship between literature and socio-political power dynamics. ABSTRAK Penelitian ini bertujuan untuk mengungkap representasi ideologi hegemonik dalam novel Saman karya Ayu Utami melalui pendekatan Analisis Diskursus Kritis. Novel Saman dipilih sebagai objek penelitian karena konteks sosio-politik Indonesia pada masa Reformasi, yang dipenuhi dengan konflik ideologis, terutama terkait dominasi patriarki, agama konservatif, dan perjuangan untuk kebebasan individu. Melalui metode kualitatif, data dikumpulkan menggunakan teknik pembacaan mendalam dan pengkodean tematik pada potongan narasi, dialog, dan deskripsi yang mencerminkan kekuatan ideologis. Hasil penelitian menunjukkan bahwa ideologi hegemonik secara kuat diwakili melalui karakter utama dan alur cerita, yang menggambarkan ketegangan antara struktur sosial yang membatasi dan upaya individu untuk mencapai kebebasan berpikir dan bertindak. Strategi diskursif, seperti penggunaan metafora, dialog kritis, dan narasi multivokal, memperkuat kritik terhadap dominasi ideologi. Novel ini juga menampilkan dimensi sosio-politik yang erat terkait dengan kondisi Indonesia, terutama bagaimana ideologi hegemonik agama dan patriarki berfungsi sebagai alat kontrol dan reproduksi kekuasaan. Selain itu, unsur-unsur perlawanan dan subversi muncul melalui sikap dan tindakan kritis karakter yang menolak ketaatan mutlak dan berusaha mengubah tatanan sosial. Temuan ini menegaskan bahwa kekuasaan ideologis tidak mutlak, dan sastra dapat menjadi medium penting untuk refleksi sosial dan perlawanan. Penelitian ini memberikan kontribusi teoritis bagi studi sastra dan analisis diskursus, serta implikasi praktis untuk memahami hubungan antara sastra dan dinamika kekuasaan sosio-politik.